The impact of parents' occupation on academic performance of secondary school students in Kuala Terengganu - Mudassir Ibrahim, Usaini; Norsuhaily, Abu Bakar (2015)
This study aims at examining how parents’ occupation does impact students’ academic performance. The main objective of the study is to analyse how formal and informal parental occupation significantly influence secondary school students’ academic performance in Kuala Terengganu, Malaysia. Descriptive Survey Research design was used in which data from 377 respondents was collected using self-administered questionnaire from 4 selected secondary schools within Kuala Terengganu. Stratified random sampling technique was used to sample the respondents. The data was analysed using regression analysis. The result is explained in three forms, demographic information, descriptive analysis and inferential analysis. The result of the study indicated that students from a parent with formal occupation perform well than those from parents with informal occupation. Finally, recommendations are given to parents, teachers, policymakers and educational administrators.